Heavy Metal Levels of Two Cyprinid Species (Cyprinus carpio and Capoeta trutta) Populated in Almus Dam Lake, Turkey - KARATAS, MEHMET; SEKER, YASAR; SEZER, METIN (Asian Journal of Chemistry, 2010)
The object of this research was to investigate the heavy metal (AI, Cd, Cr, Cu, Fe, Ni, Pb, V, Zn) levels of two Cyprinid species (Cyprinus carpio and Capoeta trutta) inhabiting Almus Dam Lake (Tokat, Turkey). Heavy metal contents of muscle, gill and gonad tissues was detected in fresh matter by atomic absorption spectrophotometer and counted in mg kg-1. The amounts of all heavy metals in gonad and gill were higher than those in muscle. Except Cu concentration, all the other heavy metal concentrations were lower in Capoeta trutta than in Cyprinus carpio. The results indicate that the fish of Almus Dam Lake are not contaminated with heavy metals and are suitable for human consumption.